Rynek usług prawniczych w Polsce - Sołtys, Bogusław (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2017)
Recently, under the influence of mechanisms of market economy, European integration process, globalization and informatization, legal services market has changed significantly. The number of legal services providers has increased and as a result the market turned from demand market to supply market. The prices of legal services have decreased as well. Even though legal services are linked to physical persons, their qualifications, skills, properties and other personal qualities, legal entities providing legal services have developed. The reason for that is the supremacy of an organization, technology and capital over knowledge and personal abilities of sole entrepreneurs. There are also new issues related to risk, unemployment, insolvency and the pressure of social protection on the legal services market. The number of disputes between legal service providers and clients has increased as well as the instances of liability of legal services providers. One of the most important tasks for the polish legislator is to remove existing barriers in legal services market, especially concerning interdisciplinary activities. It is highly relevant to balance the proportion between regulated and non-regulated legal services market. The public interest demands also that nonregulated legal services providers should be obliged at least to follow the legal ethics principles and to acquire liability insurance and to be under supervision of legal organizations.
Keywords: rynek nowoczesnych usług prawnych w Polsce; definicja usług prawnych; rynek usług prawniczych regulowanych i nieregulowanych; zawody notariuszy i zawodowych radców prawnych; adwokaci; radcy prawni; rzecznicy patentowi; doradca podatkowy; wolność gospodarcza; swoboda umów; swoboda przedsiębiorczości; swoboda świadczenia usług